2006
DOI: 10.1093/cercor/bhk030
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Systems in the Posterior Cortex of the Human Brain Revealed during Natural Sensory Stimulation

Abstract: When exposing subjects to a continuous segment of an audiovisual movie, a large expanse of human cortex, especially in the posterior half of the cerebral cortex, shows stimulus-driven activity. However, embedded within this widespread activity, there are cortical regions whose activity is dissociated from the external stimulation. These regions are intercorrelated among themselves, forming a functional network, which largely overlaps with cortical areas previously shown to be deactivated by task-oriented parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
269
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 314 publications
(291 citation statements)
references
References 62 publications
22
269
0
Order By: Relevance
“…In one there is greater attention to external stimuli in the environment, and in the other attention is focused on internal and selfrelated stimuli including self-projection into the past, such as during remembering, and selfprojection into the future, such as during future planning (Josipovic, Dinstein, Weber and Heeger 2011). These two modes of experience appear to correspond to two competing cortical brain systems; the extrinsic system that responds most to external stimuli and tasks, and the intrinsic system that responds most to internal stimuli and tasks (e.g., Golland et al 2007;Tian et al 2007). It has been shown that training in present-focused attention as part of mindfulness training increases the emphasis on the momentary self in preference to the natural bias towards the narrative self (Farb et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In one there is greater attention to external stimuli in the environment, and in the other attention is focused on internal and selfrelated stimuli including self-projection into the past, such as during remembering, and selfprojection into the future, such as during future planning (Josipovic, Dinstein, Weber and Heeger 2011). These two modes of experience appear to correspond to two competing cortical brain systems; the extrinsic system that responds most to external stimuli and tasks, and the intrinsic system that responds most to internal stimuli and tasks (e.g., Golland et al 2007;Tian et al 2007). It has been shown that training in present-focused attention as part of mindfulness training increases the emphasis on the momentary self in preference to the natural bias towards the narrative self (Farb et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Each subject was exposed to the same movie segment in two different sessions (for details see Golland et al, 2007).…”
Section: Experiments Used In the Clustering Analysismentioning
confidence: 99%
“…A parallel recruitment of task-positive and task-negative/default-network regions has been observed during several tasks, such as passive sensory stimulation [39], continuous movie viewing [40], narrative speech comprehension [41], autobiographical planning [42] and mind wandering during a sustained attention task [36]. These diverse findings suggest that characterizing brain activity as either task-positive/world-directed or task-negative/self-directed is incomplete.…”
Section: Sensorimotor Integrationmentioning
confidence: 99%
“…Although intense engagement in sensorimotor tasks can suppress the task-negative/default-network regions that also subserve self-related processing [17][18][19], one can envision situations (e.g. introspection, envisioning the perspective of others, mind wandering) in which the required mental processes call upon resources from both sets of regions and hence lead to more balanced activations between them, as indicated by recent results [36,[39][40][41][42]. Furthermore, even in situations where the dACC and lateral PFC are recruited in opposition to task-negative/default-network regions (i.e.…”
Section: Opinionmentioning
confidence: 99%